Manajemen Risiko di Sekolah Pedesaan; Adaptasi Perubahan Melalui Peningkatan Kinerja Guru: Risk Management in Rural Schools; Adapting to Change Through Teacher Performance Improvement - Khotimah, Husnul; Hefniy, Hefniy (Idarotuna : Journal of Administrative Science, 2024)
This research aims to adapt to changes in educational institutions in rural areas through the improvement of teacher performance. This article is based on the unique challenges faced by rural schools that are not experienced by urban schools, such as limited access to educational resources, inadequate infrastructure, and diverse socio-economic conditions of students. This research uses a qualitative case study approach, with data collection techniques including field observations, interviews, and document analysis. The data analysis techniques consist of three stages: data reduction, data presentation, and conclusion drawing and verification. The research results indicate that changes in the curriculum and organizational structure are important aspects of modern education. The curriculum is not only a guide for learning but also reflects the vision and mission of the education system to prepare the younger generation to face a complex world. The organizational climate aims to enhance efficiency, flexibility, and a strong foundation for sustainable growth. Evaluation and changes to the supervision assessment system are also important for creating a fair and inclusive learning environment. Technological advancement has become the main driver of life transformation, with significant implications for society and the future of education. This research is expected to provide effective insights into educational institutions.